An Introduction to the Philosophy of Bernard Lonergan - Meynell, Hugo A. author. aut Link
X, 224 p.
Keywords: This is an introduction to the philosophy of a Christian thinker of the 20th century. The author pursues his thesis through mathematics, empirical science, common sense, depth psychology and social theory, into metaphysics, ethics and natural theology.